Elasticity of demand and behaviour-based price discrimination - Esteves, Rosa Branca (2014)
Behaviour-based price discrimination (BBPD) is typically analysed in a framework characterised by perfectly inelastic demand. This paper provides a first assessment of the role of demand elasticity on the profit, consumer andwelfare effects of BBPD.Weshowthat the demand expansion effect, that is obviously overlooked by the standard framework with unit demand, plays a relevant role. In comparison to uniform pricing, we show that firms are worse off under BBPD, however, as demand elasticity increases the negative impact of BBPD on profits gets smaller. Despite a possible slight increase in the average prices charged over the two periods in comparison to uniform pricing, we show that BBPD boosts consumer surplus and that this benefit is independent of elasticity. In contrast to the welfare results derived under the unit demand assumption, where BBPD is always bad for welfare, the paper shows that BBPD can be welfare enhancing if demand elasticity is sufficiently high.